A comparison of hazard perception and hazard prediction tests across China, Spain and the UK. (January 2019) - Ventsislavova, Petya; Crundall, David; Baguley, Thom; Castro, Candida; Gugliotta, Andrés; Garcia-Fernandez, Pedro; Zhang, Wei; Ba, Yutao; Li, Qiucheng
Highlights: Hazard perception and prediction tests were designed for China, Spain and the UK. Novice and experienced drivers did not differ on the hazard perception. The hazard prediction did, however, find a difference between the driver groups. The perception test showed cultural sensitivity; the prediction test did not. Results suggest that the prediction test is a better candidate for global export. Abstract: Hazard perception (HP) is the ability to spot on-road hazards in time to avoid a collision. This skill is traditionally measured by recording response times to hazards in video clips of driving, with safer, experienced drivers often out-performing inexperienced drivers. This study assessed whether HP test performance is culturally specific by comparing Chinese, Spanish and UK drivers who watched clips filmed in all three countries. Two test-variants were created: a traditional HP test (requiring timed hazard responses), and a hazard prediction test, where the film is occluded at hazard-onset and participants predict what happens next. More than 300 participants, across the 3 countries, were divided into experienced and inexperienced-driver groups. The traditional HP test did not discriminate between experienced and inexperienced drivers, though participant nationality influenced the results with UK drivers reporting more hazards than Chinese drivers. The hazard prediction test, however, found experienced drivers to out-perform inexperienced drivers. No differences were found for nationality, with all nationalities being equally skilled at predicting hazards. The results suggest that drivers' criterion level for responding to hazards is culturally sensitive, though their ability to predict hazards is not. We argue that the more robust, culturally-agnostic, hazard prediction test appears better suited for global export.